Effects of Musical Classes on Motor Creativity According to Age, Sex, and Weight Status in Young Students: A Music-Oriented versus Conventional Education Plan - Athos Trecroci; Gabriele Signorini; Raffaele Scurati; Dario Colella; Gaetano Raiola; Marta Rigon; Pietro Luigi Invernizzi (MDPI AG, 2023)
Motor creativity can be influenced by the specificity of the school-class environments (music-based education plans) and individual characteristics. This study aimed to investigate the effects of music oriented and conventional education plans on rhythmic perceptive capacity, motor creativity, and skill- and health-related fitness components in young students according to age, sex, and weight status. One hundred sixty-three young Italian students from elementary (second and fourth grade) and middle school (sixth and eighth grade) were enrolled in the study according to their education plan (music oriented or conventional). All participants were tested for rhythmic perceptive capacity (Stambak's test), motor creativity (Divergent Movement Ability test), skill-related (Körperkoordinationstest Für Kinder), and health-related (Multistage Fitness test) components. Individuals were also considered according to age (elementary and middle school), sex, and weight status. Significant age × education plan and sex × education plan interactions (p < 0.01) were found in motor creativity (locomotor and stability skills) and motor competence (balance and jumping-like activities). No significant weight status × education plan interaction was found. The predominant role of music in the music-oriented education plan appeared to foster the ability to enhance motor creativity in elementary and middle school students compared to the conventional plan. Moreover, music-oriented experience also seems relevant for expressing and exhibiting motor competence (i.e., balance) in relation to sex.